Operational Management in Journalism: From Thematic Modeling Edition to Knowledge Management - M. N. Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Operational management in journalism is a managerial activity in which we deals with the development, use and improvement of various approaches and methods to create a media product. Today the latest computer technologies penetrate into editorial practice, so as it became possible to say about robotize journalistic work. Modern technologies reduce many routine operations, and also to provide journalists new opportunities in the search for information, its processing and analysis. So, technological innovations is changing the nature of the preparation of media products in many editorial teams, and also the style of information management processes. In this article we tried to demonstrate the possibilities of process management in the creation and implementation of media products.